2020
DOI: 10.1139/cjfas-2019-0245
|View full text |Cite
|
Sign up to set email alerts
|

Experimental demonstration of catch hyperstability from habitat aggregation, not effort sorting, in a recreational fishery

Abstract: The relationship between angler catch rates and fish abundance can contribute to or hinder sustainable exploitation of fisheries depending on whether catch rates are proportional to fish abundance or are hyperstable. We performed a whole-ecosystem experiment in which fish abundance was manipulated and paired with weekly angler catch rate estimates from controlled experimental fishing. Catch rates were hyperstable (β = 0.47) in response to changes in fish abundance. By excluding effort sorting (i.e., catch rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…Therefore, if the fish are released, the likelihood of the individual fish being recaptured multiple times through targeted fishing increases, although no study exists to support this idea. Moreover, through echo-sounding, cryptic aggregations of fish may be effectively found, increasing the likelihood of hyperstable catch rates (Dassow et al 2020 ) and generally elevated hooking mortality. However, not all anglers utilize advanced boat-based technologies due to a lack of specialization or financial commitment.…”
Section: Review Of Technological Innovations: Application and Implicamentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, if the fish are released, the likelihood of the individual fish being recaptured multiple times through targeted fishing increases, although no study exists to support this idea. Moreover, through echo-sounding, cryptic aggregations of fish may be effectively found, increasing the likelihood of hyperstable catch rates (Dassow et al 2020 ) and generally elevated hooking mortality. However, not all anglers utilize advanced boat-based technologies due to a lack of specialization or financial commitment.…”
Section: Review Of Technological Innovations: Application and Implicamentioning
confidence: 99%
“…Specifically, certain highly effective catch innovations adopted by a minority of highly avid and skilled innovators can foster overfishing once widely adopted. First, gear innovations may maintain high catch rates even when fish stocks decline, creating hyperstability in catch rates (Post et al 2002 ; Maggs et al 2016 ; Dassow et al 2020 ). Hyperstability reduces the index value of catch per unt.…”
Section: Potential Threats and Opportunities Of Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperstability has been shown to occur when fishing catches remain constant during a period of an underlying population decline (Hamilton et al, 2016), thus overestimating the true population size. In contrast hyperdepletion is where a rapidly declining fishing catch rate occurs when the underlying population remains stable (Dassow et al, 2020). Given that catches in the study reported here seem to indicate a declining population, if hyperstability is occurring it must be only reducing the magnitude of the identified change in population size.…”
Section: Discussionmentioning
confidence: 64%
“…Johnston et al., 2010; Johnston et al., 2013; Johnston et al., 2015) implicitly allow for hyperstability through effort switching (van Poorten, Walters, & Ward, 2016; Ward, Askey, & Post, 2013), though this is rarely recognized or discussed. Given the increasing evidence that hyperstability and hyperdepletion can occur in recreational fisheries due to mechanisms including habitat and spawning aggregation and effort sorting (Askey, Richards, Post, & Parkinson, 2006; Dassow et al., 2020; Mrnak, Shaw, Eslinger, Cichosz, & Sass, 2018; van Poorten et al., 2016; Ward et al., 2013), greater attention to these dynamics in our models of recreational fisheries SES seems essential.…”
Section: Resultsmentioning
confidence: 99%